Adjustable robust optimization approach for two-stage operation of energy hub-based microgrids - Shams, Mohammad H.; Shahabi, Majid; MansourLakouraj, Mohammad; Shafie-khah, Miadreza; Catalão, João P.S. (Elsevier, 2021)
Growing demand for energy carriers has led to an increased interest in developing and managing multiple energy carrier microgrids. Furthermore, the volatile nature of renewable resources as well as the uncertain electrical and thermal demands imposes significant challenges for the operation of microgrids. Motivated by this, the paper leverages a min max min robust framework for short-term operation of microgrids with natural gas network to capture the uncertainty of wind generation and electrical/thermal loads. The proposed model is linearized and solved using the column-and-constraint generation (C&CG) procedure that decomposes the framework into a master problem and a sub-problem. The master problem minimizes the unit commitment cost, while the sub-problem determines the dispatch cost associated with the worst realization of uncertainties via a max min objective function. Also, polyhedral uncertainty sets are defined with budget of uncertainty parameter that adjusts the trade-off between the operation cost and the degree of robustness. The effectiveness of the framework is assessed and discussed via a 21-node energy hub-based microgrid. It can be seen that the solution immunizes against all realizations of uncertainties, whereby increasing the budget of uncertainty and the forecast error, the system robustness is improved. Moreover, the dual variables of the sub-problem are converted to the primary variables in order to evaluate the unit commitment and energy dispatch results.
Keywords: Adjustable robust approach; Energy hub; Microgrids; Operation scheduling; Uncertainty; fi=Sähkötekniikka|en=Electrical Engineering|